An Analysis of the Evidence Underpinning the American Academy Orthopaedic Surgery Pediatrics Clinical Practice Guidelines. Issue 2 (February 2022) - Batioja, Kelsi L.E.; Nguyen, Tiffany; Anderson, J. Michael; Detweiler, Byron; Checketts, Jake; Torgerson, Trevor; Hartwell, Micah; Vassar, Matt
Abstract : Background: Randomized control trials (RCTs) serve as evidentiary support for recommendations underpinning clinical practice guidelines (CPGs) with the goal of optimizing patient care. A knowledge gap exists within scientific literature when evaluating the quality of RCTs used as evidence in the American Academy of Orthopaedic Surgery (AAOS) pediatric CPGs. We aim to evaluate the reporting quality and risk of bias in RCTs underlying AAOS Pediatric CPG recommendations. Methods: We located all AAOS Pediatric CPGs. We then extracted all RCTs from the CPG reference sections. All included RCTs were evaluated using the Consolidated Standards of Reporting Trials (CONSORT) checklist and Cochrane Collaboration risk of bias assessment tool (RoB 2.0). Descriptive statistics were recorded, and bivariate analysis was used to account for variance in CONSORT scores. A Mann-Whitney U test was completed to compare CONSORT studies published before and after 2010. Results: Three CPGs and 23 RCTs met inclusion criteria. Mean CONSORT adherence was 69.8% (21.6/31). The lowest adhered to CONSORT items were 10, 23, and 24, while items 2a, 13a, and 18 displayed the highest adherence. Ten RCTs (43.5%, 10/23) had "low" risk of bias, 5 RCTs (21.7%, 5/23) were of "some concerns, " and 8 RCTs (34.8%, 8/23) received a "high" designation for risk of bias. There were no statistically significant associations in the bivariate regression analysis or Mann-Whitney U test. Conclusions: Our results suggest that CONSORT adherence within RCTs used as evidence in AAOS Pediatric CPGs is substandard—relying on evidence that, in some cases, is >20 years old. Many of the RCTs cited as supporting evidence have a "high" risk of bias. Altogether, these CPGs may need to be updated or expanded to include more recent evidence relevant to pediatric orthopaedic surgery. Abstract : Supplemental Digital Content is available in the text.